Estratégia comercial em um ambiente de oligopólio entre Brasil e Estados Unidos: Estudo do setor siderúrgico - Costa, Edward Martins (2006)
The object of this work is to study the behavior of the international siderurgical market between Brazil and United States in the period from 1996 to 2003. This study had as theoretical grounding the Brander and Spencer model, which deals with imperfect competition incorporating the unilateral trade intervention. siderurgical was the market chosen for analysis. The Brazilian siderurgical sector is composed of high quality, industries with respect to production. On the other hand, the American’s siderurgical sector possesses obsolete industries without enough technology to increase its productive capacity. The autoregressive vectors model was used to catch the dynamic and stochastic movements of the analyzed sector, through Response Impulse Function. The results show that the strategic trade policy adopted by the USA is the best possible, confirming the theorical model and indicating a displacement of the function of reaction of the siderurgical sector’s of this country for a higher level.